A comparison of the Remedies under the CISG and German law and the effect of the Directive 1999/44/EC on German sales law - Fritzsche, Katja (Centre for Law and Society, 2026)
Today's economic developments which lead to more and more international trade relations and globalisation underline the importance and need of regulations in this field. The belief that there should be a consistent and universal form of international mercantile law which is based upon common sense and common legal principles led to the development of the United Nations Convention on Contracts for the International Sale of Goods (CISG).1 The CISG was adopted by a diplomatic conference on 11 April 19802 , entered into force on 1 January 19883 and has been accepted by 7 4 different states till today.4 It provides essential rules for the sale of goods and a regulation of issues of contract law. 5 It has to be mentioned that, in contrast to the BGB, the CISG does not apply to items, bought for personal household use, properties and ships as well as to stocks, shares, money, liquids, gas, rights and other items, for example, electricity and intellectual property rights (Article 2 CISG).